Settler Colonialism and Beyond - Greer, Allan (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2019)
The settler colonial approach has much to offer historians. However, when we consider the extended, 500-year history of the invasion of Indigenous North America, we encounter several sorts of colonialism; the settler variety stands out as a dominant force in some periods and regions, but it fades to insignificance in others. Two other versions of colonialism discussed in this article, “Imperial/Commercial Penetration” and “Extractivism,” seem particularly relevant to the history of the northern half of the continent. Along with Settler Colonialism, these two modes of colonialism made their appearance according to quite different timetables in the various regions of Canada. Extractivism, it is argued here, has become the predominant form of intrusion into Indigenous spaces in recent decades.